2022
DOI: 10.1177/07482337221133881
|View full text |Cite
|
Sign up to set email alerts
|

On the toxicity of gold nanoparticles: Histological, histochemical and ultrastructural alterations

Abstract: Gold nanoparticles (Au NPs) are used in diagnostic and therapeutic applications together with a variety of industrial purposes and in many biomedical sectors with potential risks to human health. The present study aimed to the histological, histochemical, and ultrastructural alterations induced by Au NPS in vital organs. Healthy male Wistar Albino rats ( Rattus norvegicus) were subjected to 20 injections of 10-nm Au NPs at a daily dose of 2 mg/kg. Liver, kidney, heart, and lung biopsies from control and Au NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…They showed that inflammation parameters were reduced in animals treated with the NPs but they did not find significant differences in parameters related to oxidative stress [150]. Further studies are needed to confirm its beneficial effect on MI due to its possible side effects [151].…”
Section: Cardiovascular Diseasesmentioning
confidence: 98%
“…They showed that inflammation parameters were reduced in animals treated with the NPs but they did not find significant differences in parameters related to oxidative stress [150]. Further studies are needed to confirm its beneficial effect on MI due to its possible side effects [151].…”
Section: Cardiovascular Diseasesmentioning
confidence: 98%
“…Токсичні параметри за перорального введення щурам лінії Вістар засвідчили, що розмір НЧ визначав відмінності в біорозподілі та шляхах виділення, а найдрібніші НЧ показали більш шкідливі ефекти, підтверджені їх розташуванням всередині ядра клітини і більш вираженим пошкодженням ДНК, проте їх кумуляції в статевих залозах визначено не було [32]. Au-NPs за ін'єкційного введення викликали зміни у печінці щурів (цитоліз гепатоцитів, цитоплазматична вакуолізація, гідропічна дистрофія та ядерні зміни) та інших внутрішніх органів (нирки, легені, серце) [33]. Можлива участь даних НЧ в руйнуванні ДНК статевих клітин вказує на їх потенційну РТ, що потребує детальних експериментальних досліджень.…”
unclassified